Vegetation Analysis of the Spring Water Surroundings at the Wanagama Rehabilitated Forest - Kusumandari Ambar; Marhaento Hero; Suryatmojo Hatma (BIO Web of Conferences, 2024)
Water is a basic need for all living things on earth. The existence of water on Earth cannot be separated from the hydrological cycle. The presence of vegetation has an impact on the water absorption process and protects the soil surface from the kinetic energy of rainwater. Vegetation measurements were carried out on plots measuring 8 m x 60 m. The measuring plot is made perpendicular to the contour direction or in the direction of the slope. Data processed with Ms. Excel continued with SExIFS software. Vegetation data was collected to create a profile diagram with horizontal and vertical projections as well as calculate the relative dominancy (DR), relative frequency (FR), and relative density (KR) to determine the important index (INP) value. The research results showed that the percentage of canopy cover varied from 33.13% in Tuk Umbul, followed by Sendang Tahunan and Sendang Ayu at 46.87% and 42.08%, then Sendang Mojo (74.17%) and the best is at the Salak Spring area (87.71%). The highest important index values are at teak (Tectona grandis), followed by Jabon (Neolamarckia cadamba), and Beringin (Ficus sp.).